Radiation destruction and internal friction in silicon single crystals - Ryzhikov, V.D.; Rokhmanov, N.Ya.; Galkin, S.N.; Gnap, A.K. (Вопросы атомной науки и техники, 2004)
The study of radiation defects in silicon single crystals of different orientation is carried out by means of methods of internal friction (IF) and electrical resistance. At the mechanical damping measurement a strategy of low-frequency flexible oscillations (f ~ 5 Hz) was used during the process of irradiation with α-particles. The descending curves and anomalous inverted hysteresis effect of IF versus amplitude of cyclic deformation were observed. The results were explained by the processes of ionization by induced infra-red radiation and charged dislocation-point defects association interaction. Методом внутрішнього тертя та електричного опору вивчене утворення радіаційних дефектів в монокристалах кремнію різної орієнтації. При механічному дослідженні застосовували метод низькочастотного (f~5 Гц) пружного впливу на зразки, що опромінювалися α-частками. Були виявлені спадаючі криві й аномальний інвертований ефект гістерезису зворотної амплітуди циклічної деформації. Результати можна пояснити процесами взаємодії інфрачервоних променів із зарядженими дислокаційноточковими асоціатами. Методом внутреннего трения и электрического сопротивления изучено образование радиационных дефектов в монокристаллах кремния различной ориентации. При механическом исследовании применяли метод низкочастотного (f~5 Гц) упругого воздействия на образцы, облучаемые α-частицами. Были обнаружены убывающие кривые и аномальный инвертированный эффект гистерезиса обратной амплитуды циклической деформации. Результаты можно объяснить процессами взаимодействия инфракрасных лучей с заряженными дислокационно-точечными ассоциатами.